Social Workers’ Experiences in Preparing Children for the Children’s Court: The Need for Specific Guidelines - February, Ernestine; Simeon De Jager, Elzahne (Southern African Journal of Social Work and Social Development)
The children’s court aims to protect children by acting in the best interests of the child. Another function of the children’s court is to determine whether a child needs care and protection (Children’s Act 38 of 2005). Court proceedings can be stressful for the child, who is already abused, neglected, and removed from their normal environment. There are limited resources within the South African context regarding the preparation of children for children’s court proceedings. This qualitative social work research study explored social workers’ perceptions and experiences with regard to guidelines that could assist social workers in preparing children for children’s court proceedings. The researcher conducted semi-structured interviews by following a purposive sampling method with social workers from the Department of Social Development in the Zwelentlanga Fatman Mgcawu District Municipality with the purpose of exploring the need for specific guidelines in preparing children for children’s court. The findings revealed the lack of guidelines that existed. Key themes include: social work roles in court, barriers to role fulfilment, and focus and content of guidelines.